2018
DOI: 10.1107/s2052520618013185
|View full text |Cite
|
Sign up to set email alerts
|

Triamterene–furosemide salt: structural aspects and physicochemical evaluation

Abstract: Furosemide (Fur) is a BCS class IV diuretic drug with low bioavailability due to its poor solubility and poor membrane permeability. Triamterene (Tri) is a potassium-sparing diuretic with low bioavailability due to its poor solubility. Here, a novel drug-drug salt composed of Tri and Fur was successfully synthesized. Tri-Fur was comprehensively characterized with single-crystal X-ray and powder X-ray diffraction techniques, thermogravimetric analysis, differential scanning calorimetry and dynamic vapor sorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…However, the original defects of the parent drugs are still there (discussed below). In this way, drug-drug pharmaceutical salts present an alternative method that is expected to overcome the problems associated with traditional combination drugs since they offer a way to dramatically alter physicochemical properties (Bag et al, 2014;Thorat et al, 2015;Gopi et al, 2016;Putra et al, 2016;Peng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, the original defects of the parent drugs are still there (discussed below). In this way, drug-drug pharmaceutical salts present an alternative method that is expected to overcome the problems associated with traditional combination drugs since they offer a way to dramatically alter physicochemical properties (Bag et al, 2014;Thorat et al, 2015;Gopi et al, 2016;Putra et al, 2016;Peng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have reported pharmaceutical salts and cocrystals of FUR. A search of this dataset for drug-drug multi-component crystals revealed a total of 11 systems [8,[10][11][12][13][29][30][31]. A common structural feature observed is the key role of the carboxylic group in the interaction with the coformer or counterion and the formation of other synthons involving the sulfonamide group that participates in stabilizing the crystal structure packing.…”
Section: Coformer Selectionmentioning
confidence: 99%
“…Vibrational spectroscopic techniques are important not only to differentiate the pharmaceutical cocrystals and salts (Iwata et al, 2017), but also to research the polymorphism of organic molecules (Drużbicki et al, 2015). Raman spectroscopy can be used to characterize the polymorphism of APIs (Kulkarni et al, 2012;Š asíc & Mehrens, 2012), to monitor the polymorphic feedback control of crystallization processes (Simone et al, 2014) and to discriminate the pharmaceutical salts conveniently (Peng et al, 2018(Peng et al, , 2019. FTIR and Raman spectroscopic techniques were carried out in combination for the characterization of RSV cocrystals, which provided complementary and comprehensive information.…”
Section: Vibrational Spectroscopic Studies Of Rsv Cocrystalsmentioning
confidence: 99%